Landslides and engineered slopes [electronic resource] : protecting society through improved understanding : proceedings of the 11th International and 2nd North American Symposium on Landslides and Engineered Slopes, Banff, Canada, 3-8 June 2012 - International Symposium on Landslides (11th : 2012 : Banff, Alta.); Turner, A. Keith, editor; Leroueil, Serge, editor; Eberhardt, Erik Brian, 1969- editor; Froese, Corey, editor (Leiden : CRC Press, 2012)
Includes bibliographical references and author index